Narratives in televised political ads toward alternative discourses and critical voters - Tatcho, Orville B. (Plaridel, 2023)
Access online through this link: https://www.plarideljournal.org/article/narratives-in-televised-political-ads-toward-alternative-discourses-and-critical-voters